Emergent multidrug-resistant nontyphoidal Salmonella serovars isolated from poultry in Brazil coharboring blaCTX-M-2 and qnrB or blaCMY-2 in large plasmids - Penha Filho, Rafael Antonio Casarin [UNESP]; Ferreira, Joseane Cristina; Kanashiro, Ana Maria Iba; Berchieri Junior, Angelo [UNESP]; Darini, Ana Lúcia da Costa (Elsevier, 2019)
The number of foodborne gastroenteritis caused by nontyphoidal Salmonella (NTS) worldwide is estimated to be 80.3 million each year. Currently, antimicrobial-resistant NTS disseminated in the animal environment increases the risk of aggravated foodborne outbreaks. Poultry are important source of foodborne NTS infections. This study was conducted to evaluate the phenotypic and genotypic characteristics of 83 NTS isolates from poultry, classified within 36 different serovars. The most prevalent serovar was S. Schwarzengrund (10/83), from which 8/10 were multidrug resistant (MDR). The antimicrobial susceptibility testing showed a total of 18 MDR isolates, from which 8/18 coharbored blaCTX-M-2 and qnrB5. The genes qnrB5, blaCTX-M-2, qnrB2, or blaCMY-2 were also found alone in other MDR isolates. All resistance genes were harbored in large plasmids, ranging from 30 to 270 kb. The pColE replicon was present in 8 MDR isolates; however it was not associated with resistance. ISCR1 and class I integron structures were always associated with blaCTX-M-2.
Keywords: Antimicrobial resistance; Foodborne; Infection; Salmonellosis